Electron beam irradiation of textile effluents and non-ionic ethoxylated surfactant for toxicity and color removal (Brazilian Journal of Radiation Sciences (BJRS), 2019)
Textile industry has an expressive scenario in the world economy and Brazil is the 5th in the textile production. By 2015, Brazilian textile production represented US $ 39.3 billion, accounting for more than 1.8 million tons of fabric. The effluents from textile industry are highlighted by quantity of wastewater discharged and variety of substances (dyes, bleaching agents, surfactants, salts, acids, among others). Such compounds often prove to be toxic to aquatic biota. This present study aims to assess toxicity of whole effluents, before and after irradiation (by electron beam accelerator, EBI). In addition, the reduction of the effluent color after irradiation is also very important. Daphnia similis and Vibrio fischeri were the biological systems applied for toxicity evaluations.  Previous results demonstrated the surfactant as the main toxic compound, in the untreated and irradiated forms, EC 50 = 0.44 ppm ± 0.02 (untreated); EC 50 = 0.46 % ± 0.07 (irradiated). The irradiation was effective for reducing color of the effluent, starting from 0.5 kGy. EB irradiation may be proposed as an alternative treatment for the final effluent from textile processing, mainly for reuse purposes.